Industrial architecture of Primorye. Vladivostok, Ussuriysk - Bazilevich, Mikhail; Kradin, Nikolai (project baikal, 2021)
The article presents a systematic picture of the development of industrial architecture of large cities in the south of the Russian Far East in the second half of the XIX - early XX centuries. Using the example of Vladivostok and Ussuriysk, the main features of the architecture of factories and other industrial facilities are identified, due to the specifics of the development of the region and its individual cities. The main types of industrial facilities and the principles of their placement in urban areas are considered.